ijee 2022
DOI: 10.48165/ijee.2022.58127
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Willingness of Practising Dairy Farmers sons to Work Permanently in Rural Area

Abstract: The study on the attitude and willingness of sons of the practising dairy farmers towardspermanently working in a rural area was carried on milk-producing districts of Anand andKheda of Gujarat state with 200 sample size. The study reveals that the majority (96.50%)of the sons of practising dairy farmers had a favourable to highly favourable attitude towardspermanently working in the rural area. It also concludes that the majority (80.50%) of thedairy farmers’ sons had poor overall willingness to stay physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The data point out that variables viz; family size (r = 0.217*), family income (r = 0.206*) and livelihood status (r = 0.446*) were found to be significantly and positively correlated with occupational mobility. Contradictory results were reported by Shaik & Chauhan (2022), the study revealed that annual income was non-significantly correlated with the willingness of farmer's next generation (son) to stay physically and work in the rural area. However, occupation of head of household (r = -0.199*) was found negatively and significantly associated with occupational mobility.…”
Section: Relationship Between Respondent's Socio Personal Antecedents...mentioning
confidence: 63%
“…The data point out that variables viz; family size (r = 0.217*), family income (r = 0.206*) and livelihood status (r = 0.446*) were found to be significantly and positively correlated with occupational mobility. Contradictory results were reported by Shaik & Chauhan (2022), the study revealed that annual income was non-significantly correlated with the willingness of farmer's next generation (son) to stay physically and work in the rural area. However, occupation of head of household (r = -0.199*) was found negatively and significantly associated with occupational mobility.…”
Section: Relationship Between Respondent's Socio Personal Antecedents...mentioning
confidence: 63%